Pengembangan Media Pembelajaran Multimedia Interaktif Articulate Storyline 3 Pada Mata Pelajaran Sejarah Kebudayaan Islam Di Madrasah Tsanawiyah - Nisa’, Khoirun; Solichin, Mujianto; Widiyaningsih, Puspa Mia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Students of Grade VII MTs Al-Ma’arif Brudu Sumobito Jombang in the 2025 academic year experienced a decrease in learning enthusiasm and a lack of interest in learning, especially in the SKI subject. This is due to the lack of use of learning media in the classroom. For this reason, researchers developed an interactive multimedia learning media Articulate Storyline 3 with the aim of increasing students’ enthusiasm for learning. The research method used in this article is research and development (Research and Development) with data analysis techniques using the Flow Model, and data collection techniques in the form of interviews, observations, questionnaires and tests. The results of this study indicate that the Articulate Storyline 3 learning media is declared effective in learning SKI class VII MTs Al-Ma’arif Brudu Sumobito. This can be seen from the recapitulation of the average score of media design expert validation of 100%, material expert validation of 100%, and practitioner validation of 100%. Furthermore, the results of the trial usage in trial 1 and trial 2 also proved that the Articulate Storyline 3 learning media can increase students’ enthusiasm as evidenced by the results of the N-Gain test on student scores of 0.75. In addition, based on the results of the student response questionnaire analysis, the total average percentage result was 92.96%, which means that the Articulate Storyline 3 learning media is included in the very interesting category.